The Adenosinergic System A Non-Dopaminergic Target in Parkinson's Disease - Morelli, Micaela; Simola, Nicola; Wardas, Jadwiga (Current Topics in Neurotoxicity, 2015)
Adenosine A2A receptor antagonists have shown great promise in the treatment of Parkinson's Disease and alleviation of symptoms. This book addresses various aspects of this class of drugs from their chemical development to their clinical use. Among the many insightful chapters contained in this book, there are three unique reviews that have not previously been published in any format: (1) a history of istradefylline, the first A2A antagonist approved for treatment of Parkinson's Disease, (2) an overview of neuroimaging studies in human health and disease, and (3) a study of urate as a possible biomarker and neuroprotectant.